Optimal scheduling strategy of EVs considering the limitation of battery state switching times - Lizi Luo; Pinquan He; Suyang Zhou; Guannan Lou; Bin Fang; Puyu Wang (Energy Reports, 2022)
In recent years, with environmental problems being increasingly outstanding, the clean transport represented by electric vehicles (EVs) has replaced traditional fossil fuel vehicles in an inevitable way. Taking advantage of the bidirectional charging power of EVs is an effective measure to avoid the grid shock caused by the large-scale EV penetration. However, the frequent charging and discharging of EVs will bring unnecessary damage to the batteries. In order to solve this problem, the paper proposes an optimal scheduling strategy of EVs considering the limitation of battery state switching times. Besides the traditional constraints relevant with EVs’ scheduling, the limitation of battery state switching times is properly involved in the proposed strategy. Numerical results show that the charging schemes obtained from the proposed scheduling model can protect EV batteries at an almost negligible loss in users’ charging cost.